A season for second chances - Bayliss, Jenny (New York : G.P. Putnam's Sons, 2021)
"A charmingly quirky seaside town offers a recently separated restauranteur a fresh start and possibly a new lease on love."--
Keywords: Women cooks -- Fiction; Architects -- Fiction; Restaurateurs -- Fiction; Christmas fiction; Romance fiction